2015
DOI: 10.1038/nature14132
|View full text |Cite
|
Sign up to set email alerts
|

New genetic loci link adipose and insulin biology to body fat distribution

Abstract: Body fat distribution is a heritable trait and a well-established predictor of adverse metabolic outcomes, independent of overall adiposity. To increase our understanding of the genetic basis of body fat distribution and its molecular links to cardiometabolic traits, we conducted genome-wide association meta-analyses of waist and hip circumference-related traits in up to 224,459 individuals. We identified 49 loci (33 new) associated with waist-to-hip ratio adjusted for body mass index (WHRadjBMI) and an additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

61
1,469
6
17

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 1,443 publications
(1,577 citation statements)
references
References 96 publications
61
1,469
6
17
Order By: Relevance
“…We therefore investigated whether LTL predicts changes in insulin resistance independent of BMI, by adding BMI to the models in ESM Table 1. The BMI effect may differ between the sexes [27,28]; therefore, we also tested the interaction between sex and BMI in these models. A higher BMI was associated with a larger increase in insulin resistance, but adding BMI to the model in ESM Table 1 had little effect on the association between LTL at baseline and change in insulin resistance (ESM Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…We therefore investigated whether LTL predicts changes in insulin resistance independent of BMI, by adding BMI to the models in ESM Table 1. The BMI effect may differ between the sexes [27,28]; therefore, we also tested the interaction between sex and BMI in these models. A higher BMI was associated with a larger increase in insulin resistance, but adding BMI to the model in ESM Table 1 had little effect on the association between LTL at baseline and change in insulin resistance (ESM Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we considered the MR analyses viable and obtained summary statistics for circulating PAI‐1 levels, CHD and CHD risk factors from previous GWASs as listed in Table 1. These are based on the largest GWAS meta‐analysis for each phenotype at the time of analysis and primarily conducted on European ancestry samples 28, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42…”
Section: Methodsmentioning
confidence: 99%
“…Like the FGF21 allele, for some of these alleles the apparent paradox is explained by the higher fat mass being concentrated in the lower body, at least in women, (e.g. those in or near FAM, LYPLAL1, GRB14) [35].There are two further limitations to our study that also mean caution is needed when translating the human genetic findings to implications for FGF21 therapies. First, despite being in the exon of FGF21, we cannot rule out the possibility that the variant associated with macronutrient intake operates through a nearby gene, and we note that the rs838133 allele is associated with the expression of a nearby gene FUT2, involved in vitamin B12 metabolism [38].…”
mentioning
confidence: 69%
“…The FGF21 rs838133 minor allele is not the first common allele to be associated with apparently paradoxical effects on fat mass and metabolic markers. Previous human genetic studies of alleles associated with insulin sensitivity have shown that most are also associated with an apparently paradoxical higher fat mass (and the insulin resistance allele is associated with lower fat mass) [32][33][34][35][36][37]. Like the FGF21 allele, for some of these alleles the apparent paradox is explained by the higher fat mass being concentrated in the lower body, at least in women, (e.g.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation